Lobular panniculitis as a manifestation of pancreatitis. Difficulties in diagnosis - O. N. Egorova; A. L. Maslovsky; I. A. Zelenov; A. N. Goryachev; B. S. Belov (Научно-практическая ревматология)
The clinical picture of lobular panniculitis associated with damage to the pancreas can vary widely, accompanied by damage to the joints and internal organs, which complicates the diagnosis of the disease. A clinical observation of a torpid course of lobular panniculitis with total damage to organs and systems is presented, which clearly illustrates the difficulties of differential diagnosis and therapy that arise in real therapeutic practice.